Analisis Kebijakan Presiden Nayib Bukele dan Implikasi Terhadap Turunnya Kriminalitas di El Savador - Muhammad Ghiyas Gaspah; Agussalim Burhanuddin (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study analyzes the security policies implemented by President Nayib Bukele in El Salvador and their implications for crime rates and democratic institutions. Using a decriptive qualitative approach, the study finds that although crime has significantly declined, it has come at the cost of weakned democratic instutions, rising electoral authoritarianism, and the use of fear-based politics to gain public legitimacy. Mass detentions, reduced civil liberties, and the centralization of executive power show that stability is being built not through repressive control. Furthermore, vulnerable groups such as the poor and women are disproportionately affected between public security and human rights protection to avoid deepening structural inequalities and creating new forms of social vulnerability.